Single‐Beat Estimation of Right Ventricular Contractility and Its Coupling to Pulmonary Arterial Load in Patients With Pulmonary Hypertension - Ryo Inuzuka (Wiley, 2018)
BackgroundAn accurate assessment of intrinsic right ventricular (RV) contractility and its relation to pulmonary arterial load is essential for the management of pulmonary hypertension. The pressure‐volume relationship with load manipulation is the gold standard assessment used for this purpose, but its clinical application has been hindered by the lack of a single‐beat method that is valid for the human RV. In the present study, we sought to validate a novel single‐beat method to estimate the preload recruitable stroke work (PRSW) and its derivative for ventriculoarterial coupling in the human RV. Methods and ResultsA novel single‐beat slope of the PRSW relationship (Msw) was derived by calculating the mean ejection pressure when the end‐systolic volume was equal to volume‐axis intercept of the PRSW relationship. In addition, by using a mathematical transformation of the equation representing the linearity of the PRSW relationship, a novel index for ventriculoarterial coupling, Msw/mean ejection pressure, was developed. RV pressure‐volume relationships were measured in 31 patients (including 23 patients with pulmonary hypertension) who were referred for right‐sided heart catheterization. In this cohort, the single‐beat Msw was strongly correlated with the multiple‐beat Msw (r=0.91, P<0.0001). Moreover, a significant correlation was observed between the single‐ and multiple‐beat Msw/mean ejection pressure (r=0.53, P=0.002), with a stronger correlation in those with greater RV systolic pressure (r=0.70, P=0.003). ConclusionsThe novel single‐beat approach provided an accurate estimation of indexes for the PRSW relationship and ventriculoarterial coupling. It may be particularly useful in assessing RV adaptation to increased pressure overload.